Beiträge zum Wortschatz des Alten Testaments: Liwyatan (לִוְיַתַן) und Nəhūštān (נְחֻשְׁתָּן) - Theis, Christoffer (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The article examines the theory of Manfred Görg, who postulated two Egyptian loanwords in the Old Testament in 2003. By an inclusion of phonetic laws, sound changes and cultural-historical aspects, the theory that Liwyatan (לִוְיַתַן) and Nəhūštān (נְחֻשְׁתָּן) are Egyptian loanwords must be rejected.